2019
DOI: 10.1107/s2052520619006243
|View full text |Cite
|
Sign up to set email alerts
|

The incommensurately modulated structures of volcanic plagioclase: displacement, ordering and phase transition

Abstract: Four basaltic phenocryst samples of plagioclase, with compositions ranging from An 48 (andesine) to An 64 (labradorite), have been studied with single-crystal X-ray and neutron diffraction techniques. The samples were also subjected to a heating experiment at 1100 C for two weeks in an effort to minimize the Al-Si ordering in their structures. The average and the modulated structures of the samples (before and after the heating experiment) were compared, in order to understand the mechanism of the phase transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The e-reflections in the volcanic phenocrysts are normally weak and diffuse; therefore, the q-vectors are relatively poorly defined. The q-vectors also depend on the ordering states of the structure as discovered by Jin, Xu et al (2019). We suggest calling these volcanic phenocryst e-plagioclases with diffuse and 'moving' satellite peaks e , to separate them from the e and e structures where the q-vectors do not change with research papers Acta Cryst.…”
Section: Figure 11mentioning
confidence: 79%
See 1 more Smart Citation
“…The e-reflections in the volcanic phenocrysts are normally weak and diffuse; therefore, the q-vectors are relatively poorly defined. The q-vectors also depend on the ordering states of the structure as discovered by Jin, Xu et al (2019). We suggest calling these volcanic phenocryst e-plagioclases with diffuse and 'moving' satellite peaks e , to separate them from the e and e structures where the q-vectors do not change with research papers Acta Cryst.…”
Section: Figure 11mentioning
confidence: 79%
“…B76, 93-107 ordering states. Jin, Xu et al (2019) speculated that all disordered C " 1 1 structures start showing e-reflections around the same positions in reciprocal space, independent of the composition, which are governed by the Anti-Rigid Unit Modes (ARUM) of the tetrahedral framework. The q-vector moves towards the e line as the modulation gets stronger in the structure.…”
Section: Figure 11mentioning
confidence: 99%
“…The subsolidus phase relations of plagioclase feldspar solution has been most comprehensively summarized by Carpenter [13] (Figure S16), taking into consideration all the reported experimental data and natural samples available at the time. There are, however, some inconsistencies between the labradorite region in Carpenter's phase diagram and some recent discoveries regarding the incommensurately modulated structures of e-plagioclase [14,15,23,29,30,32]. The new data reported in this paper regarding the Bøggild intergrowth also provide some new insights to the subsolidus phase relations of the low-temperature intermediate plagioclase, as is discussed below.…”
Section: Discussionmentioning
confidence: 57%
“…The first phase relation to be discussed is that between the e1 and e2 phases. Recent studies [15,23,30,32] have shown that the e2 structure can be ordered into the e1 structure…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation